2023
DOI: 10.3390/jcm12082862
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and the Temporomandibular Joint—Preliminary Observations

Abstract: (1) Background: The complete picture of the disease is not fully recognized and extends far beyond the pelvis. The disease’s impacts lead to systemic inflammation, in turn resulting in sensitization to pain. The aim of this study was to check whether statistical correlations exist in women with endometriosis with regard to their experience of pain: headache, pelvic pain, temporomandibular joint pain, along with teeth clenching and the treatment of the disease. We constructed contingency tables, followed by Pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Nejati et al [ 30 ] also demonstrated the effectiveness of a physiotherapy program that includes therapeutic exercise in the treatment of sacroiliac dysfunctions, further supporting the use of therapeutic exercise as a technique for improving mobility and reducing pain. Is this line, it interesting to highlight that current research has shown that TMDs may be related to the pelvis in disorders such as endometriosis [ 31 ]. Furthermore, a recent study has revealed correlations between the presence of pain on the right and left sides of the pelvis and pain on the right and left sides of the TMJ, teeth clenching and TMJ pain, the occurrence of pelvic pain and the treatment modality for endometriosis performed, and the presence of pain in other parts of the body but the pelvis and the treatment that the patient received for endometriosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nejati et al [ 30 ] also demonstrated the effectiveness of a physiotherapy program that includes therapeutic exercise in the treatment of sacroiliac dysfunctions, further supporting the use of therapeutic exercise as a technique for improving mobility and reducing pain. Is this line, it interesting to highlight that current research has shown that TMDs may be related to the pelvis in disorders such as endometriosis [ 31 ]. Furthermore, a recent study has revealed correlations between the presence of pain on the right and left sides of the pelvis and pain on the right and left sides of the TMJ, teeth clenching and TMJ pain, the occurrence of pelvic pain and the treatment modality for endometriosis performed, and the presence of pain in other parts of the body but the pelvis and the treatment that the patient received for endometriosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the high cost of treatment in each country, it is certainly the case that non-pharmacological methods/ procedures to reduce pain among women with endometriosis and thus physiotherapeutic methods/procedures to improve the quality of life of women can be a good solution for the economics of medical care but especially for the affected women. Physiotherapy methods/symptoms are also noninvasive treatment procedures and the authors therefore emphasise their signifance for practical application [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Although it may present asymptomatically in some women ( Burney & Giudice, 2012 ), the disease may be associated with the presence of symptoms such as dysmenorrhea, deep dyspareunia, dysuria, chronic pelvic pain, and irregular uterine bleeding ( Taylor, Kotlyar & Flores, 2021 ; Vercellini et al, 2007 ; Burney & Giudice, 2012 ). A common symptoms includes the sensation of weight in the lumbosacral region of the spine and lower limbs ( Bulletti et al, 2010 ), but it can also affect other body parts, being associated with headaches and temporomandibular joint pain ( Wójcik et al, 2023 ). These symptoms characterize the disease as a debilitating condition that affects daily life, including professional and personal activities ( Hirsch et al, 2020 ; Vercellini et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms characterize the disease as a debilitating condition that affects daily life, including professional and personal activities ( Hirsch et al, 2020 ; Vercellini et al, 2007 ). In addition, pain can impair social relationships and generate mood changes ( Burney & Giudice, 2012 ; Wójcik et al, 2023 ; Della Corte et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%